Correlation between the preoperative state of nutrition and the frequency of postoperative problems after video-assisted gastrostomy in children. - Einar Ólafur Arnbjörnsson; Torbjörn Backman; Helen Sjövie; Carl-Magnus Kullendorff (Gastroenterology Insights, 2009)
Gastrostomy operations are performed on children referred to the pediatric surgical clinic without being influenced by the patient’s state of nutrition. This has been motivated by the idea that a gastrostomy would enable a fast and secure improvement in this regard. The question arises whether an improvement in the preoperative nutritional status would reduce the number of postoperative complications. The aim of the study was to test the hypothesis that the frequency of postoperative complications after a video-assisted gastrostomy is correlated to the child’s preoperative state of nutrition. Fifty consecutive children with severe nutritional problems underwent a video-assisted gastrostomy operation where gastrostomy buttons were placed as the initial surgical feeding tube. At the time of the operation, the children’s nutritional parameters were registered routinely. After the operation, the children were followed up prospectively for six months and all complications were documented according to a protocol. The children were ranked according to the severity and frequency of postoperative complications and problems. Correlation to nutritional parameters was calculated. The children did not present with any serious postoperative intra-abdominal complications. There was a significant correlation between the frequency of minor complications and the child’s state of nutrition, measured as the number of standard deviations from normal length and weight as well as phosphate, magnesium, and iron levels in the blood. This study revealed a significant correlation between the patients’ state of nutrition and the postoperative complications during the first postoperative six months. Thus, the findings support a routine of nutritional evaluation prior to performing a gastrostomy operation.